PENGARUH TINGKAT PENDIDIKAN, PENGANGURAN DAN BELANJA MODAL TEHADAP PDRB DAN KEMISKINAN KABUPATEN/KOTA DI PROVINSI BALI - Putri Suastini, Nyoman Ayu; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 1 (2021): VOL 10 NO 1, JANUARI 2021 [ 1 - 450 ], 2021)
Pover ty is a problem in multidimensional development. Poverty is a complex problem related to various dimensions, namely social, economic, cultural, political as well as the dimensions of space and time. Poverty in the Province of Bali is still a problem for districts / cities in the Province of Bali. The objectives in this study are (1) to analyze the effect of education level, unemployment and capital expenditure on district / city GRDP in Bali Province, (2) analyze the influence of education level, unemployment, capital expenditure and GRDP on district / city poverty in Bali Province, and (3) indirectly analyze the level of education, unemployment and capital expenditure on poverty through regency / city GRDP in Bali Province. This research was conducted in districts / cities of Bali Province. This study uses secondary data with path analysis techniques. The results of this study stated that (1) the level of education and capital expenditure had a significant positive effect on GRDP of Regency / City in Bali Province, but unemployment had a significant negative effect on GRDP of Regency / City in Bali Province, (2) the level of education and capital expenditure had a significant negative effect to district / city poverty in Bali province, but unemployment and GRDP have a significant positive effect on district / city poverty in Bali Province, (3) GRDP mediates the relationship between education level and capital expenditure to district / city poverty in Bali province, but GRDP does not mediate the relationship unemployment towards poverty in Regency / City in Bali Province. Keywords : education level, unemployment , capital expenditure, GRDP and poverty.